2012
DOI: 10.2478/s11658-011-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between plant polyphenols and the erythrocyte membrane

Abstract: The purpose of these studies was to determine the effect of polyphenols contained in extracts from apple, strawberry and blackcurrant on the properties of the erythrocyte membrane, treated as a model of the biological membrane. To this end, the effect of the substances used on hemolysis, osmotic resistance and shape of erythrocytes, and on packing order in the hydrophilic region of the erythrocyte membrane was studied. The investigation was performed with spectrophotometric and fluorimetric methods, and using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
1
13
0
2
Order By: Relevance
“…Indirect effects of polyphenols against oxidative stress were previously suggested, based on their ability to stimulate activity of antioxidant enzymes and modulate cell signaling pathways and gene expression [ 40 ]. Additionally, protective effects of polyphenols against membrane lipid oxidation were associated with their interaction with the lipid phase of erythrocyte membrane and incorporation in outer hydrophilic part [ 12 , 13 ]. As far as authors are aware data on direct effects of glucomannan intake on oxidative status or membrane fatty acid profile in humans are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect effects of polyphenols against oxidative stress were previously suggested, based on their ability to stimulate activity of antioxidant enzymes and modulate cell signaling pathways and gene expression [ 40 ]. Additionally, protective effects of polyphenols against membrane lipid oxidation were associated with their interaction with the lipid phase of erythrocyte membrane and incorporation in outer hydrophilic part [ 12 , 13 ]. As far as authors are aware data on direct effects of glucomannan intake on oxidative status or membrane fatty acid profile in humans are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Due to high content of unsaturated bonds as the main site of free radicals attack, PUFAs are fatty acids susceptible to oxidative damage. Since biological membranes are the first line of cell contact with extracellular substances, including free radicals [ 12 ], it is of special importance to determine their fatty acid profile and status of PUFAs. Recent studies revealed that polyphenol-rich plant extracts protect biological membranes from oxidative damage by scavenging free radicals in the medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of osmotic resistance studies on erythrocytes treated with the extracts have shown that the erythrocyte membrane, possibly as a result of sealing, becomes more resistant to changes in osmotic pressure. A higher osmotic resistance of erythrocytes treated with other plant extracts is found by Cyboran et al ( 2012 , 2014 ), He et al ( 2008b ), and Wang et al ( 2001 ). The increase in osmotic resistance of BS- and BH-modified RBC can be explained by the fact that polyphenolic compounds present in the extracts become incorporated mainly in the polar region of the lipid bilayer, as evidenced by the results of the fluorimetric research, shape, or FTIR studies presented in this paper, as well as our earlier work (Włoch et al 2013 ).…”
Section: Discussionmentioning
confidence: 69%
“…The hemolytic studies have shown that the extracts, in a wide range of concentrations, not only do not act destructively on the MRBC, without causing hemolysis of RBC, but strengthen it. The absence of hemolytic toxicity of different polyphenolic extracts is shown by Bonarska-Kujawa et al ( 2014 ), Cyboran et al ( 2012 ), and Suwalsky et al ( 2007 ). These results allow believing that polyphenolic compounds present in the extracts do not penetrate deeply into the MRBC, since hemolytic action is caused by hydrophilic–hydrophobic molecules whose alkyl chains penetrate the hydrophobic region of the lipid bilayer, weakening the interaction between components of the membrane (Kleszczyńska et al 1986 ; Łuczyński et al 2013 ).…”
Section: Discussionmentioning
confidence: 91%